If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 + -1(5 + -4x) = 3 2x + 7 + (5 * -1 + -4x * -1) = 3 2x + 7 + (-5 + 4x) = 3 Reorder the terms: 7 + -5 + 2x + 4x = 3 Combine like terms: 7 + -5 = 2 2 + 2x + 4x = 3 Combine like terms: 2x + 4x = 6x 2 + 6x = 3 Solving 2 + 6x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6x = 3 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 3 + -2 6x = 3 + -2 Combine like terms: 3 + -2 = 1 6x = 1 Divide each side by '6'. x = 0.1666666667 Simplifying x = 0.1666666667
| -9(16-f)=(1-3f) | | 2a-2b-3c=1.5 | | -x-7=-8+x | | z-8=0 | | x-20=3y | | 2x(2x-1)=5 | | f(x)=10x^2-20x+16 | | k-3=8 | | x+4/x+7 | | 7n+10=78 | | 4(2x-3)=8+(2x-4) | | 1/4-5=27 | | X^6-2x^4-x^2+2=0 | | (n-5)*7=70 | | 4x^2-23x+72=0 | | 3+2i/6+5i | | 6x/38=48 | | 0=x^2+4x-32 | | x^2-19x+25=0 | | 0=x^2+10x+24 | | 1.24=x2-x1/3 | | 0=(x-4)(x+2) | | 3x=999 | | 2x=7.81 | | 3x+5+2=20 | | n*6=126 | | y/16*4y^2/y^2 | | n+3=55 | | n+36=59 | | -2x-2=5 | | 2x+1-3x-3+x=10-2x | | 6(x+4)=7x-8 |